2021
DOI: 10.3390/antibiotics10070781
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Meropenem/Vaborbactam Plus Fosfomycin Treatment of KPC Producing K. pneumoniae Septic Thrombosis Unresponsive to Ceftazidime/Avibactam: From the Bench to the Bedside

Abstract: Gram-negative bacilli septic thrombosis (GNB-ST) represents a subtle and often misleading condition, potentially fatal if not recognized early and requiring prolonged antimicrobial therapy and anticoagulation. Herein, reported for the first time, is a very challenging case of Klebsiella producing carbapenemase (KPC)-producing K. pneumoniae (KPC-Kp) ST unresponsive to ceftazidime/avibactam (CZA) relapsed first with meropenem/vaborbactam (MVB) monotherapy and subsequently cured with MVB plus fosfomycin (FOS) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“… 1 Nowadays, the treatment of KPC- Kp infections is mainly based on ceftazidime/avibactam, which undoubtedly represented a therapeutic advance in the field and contributed to the reduction of mortality rates compared with traditional therapies. 2 Nevertheless, its efficacy may be reduced in particular conditions, such as pneumonia, continuous renal replacement therapy, 3 delayed source control 4 and septic thrombosis, 5 where a risk of underexposure and, therefore, clinical failure exists, raising the question of the optimal use of this drug.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Nowadays, the treatment of KPC- Kp infections is mainly based on ceftazidime/avibactam, which undoubtedly represented a therapeutic advance in the field and contributed to the reduction of mortality rates compared with traditional therapies. 2 Nevertheless, its efficacy may be reduced in particular conditions, such as pneumonia, continuous renal replacement therapy, 3 delayed source control 4 and septic thrombosis, 5 where a risk of underexposure and, therefore, clinical failure exists, raising the question of the optimal use of this drug.…”
Section: Introductionmentioning
confidence: 99%
“…Shields et al found that pneumonia was an independent risk factor for CZA clinical failure, while the receipt of renal replacement therapy (RRT) predicted microbiological failure and CZA resistance development [ 39 ]. Recently, clinical and microbiological failures with CZA have combined to the development of decreased susceptibility/resistance to this agent, as described in a case of septic thrombosis, a high clinical complexity condition [ 43 ], and in a case of delayed source control [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although oral fosfomycin administration dates back to the 1970s and some mechanisms of resistances are unknown—as aforementioned—fosfomycin-resistant E. coli are still rare, testifying the slow adaptation rate of the bacteria to this molecule, a clear advantage for the physician. Moreover, the mechanism of action of fosfomycin, affecting the early steps involved in bacterial cell wall formation [ 48 ], suggests an additive or synergistic action in combination with other antibiotics; in fact, fosfomycin shows important synergistic effects with many other antibiotics, e.g., piperacillin/tazobactam, ceftazidime/avibactam, meropenem, colistin, and daptomycin, as well as linezolid [ 14 , 44 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Rationale For Oral Fosfomycin Administration In Patients Wit...mentioning
confidence: 99%